2016
DOI: 10.1109/tdsc.2015.2399304
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Communications under Broadband Reactive Jamming Attacks

Abstract: A reactive jammer jams wireless channels only when target devices are transmitting; Compared to constant jamming, reactive jamming is harder to track and compensate against [2], [42]. Frequency Hopping Spread Spectrum (FHSS) and Direct Sequence Spread Spectrum (DSSS) have been widely used as countermeasures against jamming attacks. However, both will fail if the jammer jams all frequency channels or has high transmit power. In this paper, we propose an anti-jamming communication system that allows communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 36 publications
(45 reference statements)
0
37
0
Order By: Relevance
“…Reactive jamming is a stealthy jamming approach in which the jammer first senses the spectrum and jams only when she detects an ongoing transmission. Due to the effectiveness and difficulty to be detected, reactive jammers are considered as the most harmful [16], [17]. Furthermore, as OFDM is used in many actual systems (and will be used at least in the first deployments of 5G), in our analysis we assume a BF-AWGN channel as in [11].…”
Section: Mim In W-skg Systems: Injection Attacksmentioning
confidence: 99%
“…Reactive jamming is a stealthy jamming approach in which the jammer first senses the spectrum and jams only when she detects an ongoing transmission. Due to the effectiveness and difficulty to be detected, reactive jammers are considered as the most harmful [16], [17]. Furthermore, as OFDM is used in many actual systems (and will be used at least in the first deployments of 5G), in our analysis we assume a BF-AWGN channel as in [11].…”
Section: Mim In W-skg Systems: Injection Attacksmentioning
confidence: 99%
“…There have been numerous analyses of proactive and reactive jamming attacks in wireless systems [27], the main difference between the two being whether the malicious node injects jamming signals constantly or during certain parts of the communication cycle. It has been found that standard methods for identifying and pro-tecting against reactive jamming attacks can fail because of the low energy required to launch the attack compared to proactive jamming.…”
Section: Jamming Attacksmentioning
confidence: 99%
“…Existing works The research work reported in this paper (corresponding author: Pinyi Ren) is supported by the National Natural Science Foundation of China (NSFC) under Grant No. 61431011. mainly focus on reactive jamming detection [7] and a few countermeasures have been proposed, such as utilization of timing channel [8], protocol design [9], and reactive jamming avoidance oriented schemes [10], [11].…”
Section: Introductionmentioning
confidence: 99%